Inventory System Design Using the First In First Out Method - Putra, M Riski; Prawiro, Radius (Journal of Computer Scine and Information Technology, 2024)
The use of computers is growing rapidly in all fields according to the progress of the times, resulting in many changes in human life in dealing with every problem that occurs and is related to the development process as a whole. One of the developments in the business sector is the Inventory System. Businesses operating in the field of drug sales still use the method of stocking goods, where when one of the stocks of a drug runs low, it will be immediately stocked. The information system that will be created for drug supplies uses the First In First Out (FIFO) method. The FIFO method means that the company will first use old/first-in stock for sales. It is hoped that this research will help leaders and employees manage drug stock transaction data efficiently.